THE PHILOSOPHICAL IMPLICATIONS OF YÄJNA AND SACRIFICIAL FIRE: A CRITIQUE - Sujatha, V (Journal of Dharma, 2001)
Vedic sacrifices are an ancient religious institution. The Vedas and their allied works are intimately related to them. Hence, an understanding of the Vedic sacrificial system and the role of fire in the context of rituals will definitely help us to understand and esteem not only the Vedas, but also the Upanishads.